Design as a contributor to chemical process accidents - Kidam, Kamarizan (2012)
The paper discusses the design errors in chemical process industry (CPI) by analyzing major equipment related accident cases from Failure Knowledge Database (FKD). The aim is to recognize the contribution of design to chemical process accidents and to evaluate the time of occurrence of the errors in a plant design project. The analysis of accident cases found out that the contribution of design to accidents is very significant: 79% of accident cases analyzed were contributed by design errors. The most critical design errors were poor layout (17%), insufficient consideration of chemical reactivity and incompatibility (16%) and incorrectly chosen process conditions (16%). The design errors were initiated at basic (32%), detailed (32%) and preliminary (22%) design phases of the project. Errors in fundamental aspects of chemical processes e.g. route selections are more severe (as compared to others errors class) and might creates many similar errors in later phases of design project. Based on the accident information gathered, a straightforward point-to-look list for error detection and elimination was suggested for process lifecycle stages.